A comparative study on Aspen Hysys interconnection methodologies. (June 2022) - Santos Bartolome, Pedro; Van Gerven, Tom
Highlights: The connection capabilities of Aspen Hysys are analyzed, and four automation approaches proposed for testing. The performance of these strategies is tested with the tools Microsoft Excel, Matlab, Python and Unity. Experiments show spreadsheet connection to be the only approach reliably functional in the four programs. The code is made available for use. Abstract: Researchers often find the need to integrate commercial process simulators such as Aspen Hysys, Aspen Plus, PRO/II or others with their own applications. However, despite the relevance of these tools, the authors have found no systematic research on connection methodologies, a gap in literature that they aim to address with this work. The authors will study the connection methodologies of the popular process simulator Aspen Hysys with four tools that hold current or potential use for chemical engineering researchers: Microsoft Excel (VBA), Matlab, Python and Unity (C#). Four different communication approaches are presented (direct communication, indirect communication, internal spreadsheets, and data tables), with results being compared in terms of accuracy of communication, time of exchange, and deviation in the results. The code used in the experiments is made available to the readers.